A Low Cost Baby Incubator Design Equipped with Vital Sign Parameters - Lamidi Lamidi; Abd Kholiq; Muslim Ali (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
A baby incubator is a heating device for premature babies so that the baby's temperature matches the temperature in the mother's womb. Premature babies are babies born in abnormal conditions where the baby's body size is below average or the gestational age has not reached 9 months. The aim of this study was to create a compact system at a low cost in an infant incubator. Apart from stabilizing the temperature, it can also calculate the premature baby's heart rate and oxygen saturation value. The contribution of the system being built can detect the early symptoms of congenital abnormalities so that abnormalities detection becomes more practical. The temperature stability in this system uses a threshold system, where the sensor readings are compared with the set point value. Meanwhile, the SpO2 system uses a finger sensor attached to the baby's finger to detect oxygen saturation and heart rate. The signal from the sensor is processed in a signal conditioning circuit consisting of an astable circuit, filter and amplifier, LPF, and demultiplexer. Based on the results of testing and measurement, the difference produced by this tool is only 0.13 - 0.182 ° C. The biggest error in the system is 0.517%. Measurement of skin temperature was carried out on 10 respondents with an average value of 34.825 ° C. so that the difference generated from this tool is only 0.175 ° C, the difference on the Humidity parameter is 0.21%. The average BPM reading of respondent 1 was 81 beats per minute and the average SpO2 value was 97%. The average BPM reading of respondent 2 was 83 beats per minute and the average SpO2 value was 98%. You can see that the module with the Arduino control system can work automatically and is able to adjust the stability of the baby incubator according to the settings. In addition, the BPM and SpO2 systems are within tolerance so they can be used for patient measurements